The effects of accounting standards on the financial reporting properties of private firms: evidence from the German Accounting Law Modernization Act - Julia Zicke; Florian Kiy (Business Research, 2017)
This study investigates whether the 2009 German Accounting Law Modernization Act has affected the reporting and accounting practices of German private firms. In reforming German accounting standards, numerous accounting options were deleted, several accounting rules were transferred from IFRS to German GAAP with some modifications, and disclosure requirements were extended. In our analysis, we examine the changes in financial reporting and their effects on disclosures. We use four financial reporting property measures: discretionary accruals, the correlation between operating cash flow and accruals, the persistence of earnings, and the predictability of earnings. The results reveal no change across all financial reporting properties. Examining disclosure compliance for capitalized development costs and other provisions reveals substantial variation in compliance.
Keywords: 650; German Accounting Law Modernization Act; German GAAP; Accounting standards; Financial reporting properties; Private firms